Hormonal Contraceptive Use and the Prevalence of Endometriotic Lesions at Different Regions within the Peritoneal Cavity. (20th January 2014) - McKinnon, Brett D.; Bertschi, Dominic; Wanner, Juilette; Bersinger, Nick A.; Mueller, Michael D.
Abstract : Endometriosis is an estrogen-dependent disease that can lead to chronic pain and subfertility. Endometriotic lesions found in different locations are heterogeneous and may represent a collection of related but distinct conditions. Whether there is a relationship between hormonal contraceptive (HC) use and endometriosis is still controversial. The purpose of this study was to determine whether HC use affected the prevalence of endometriotic lesions differently based on lesion location. Data was retrospectively collected from 161 patients presenting to the Berne University Women's Hospital between 2008 and 2012 for laparoscopic investigation. Women with histologically proven endometriosis were included in the study and patients were grouped according to lesion location and HC use. The results of the study indicate that HC users are significantly less likely to have endometriotic lesions on the ovaries, although in contrast, no difference was observed in the incidence of lesions in the rectovaginal septum (RVS) or peritoneal region. In addition, women using HC who were diagnosed with endometriotic lesions on the peritoneum were significantly younger than women with lesions in other locations. In conclusion, women with endometriosis who are currently using HC are less likely to have ovarian endometriotic lesions than in alternate locations.